2020
DOI: 10.1186/s13023-020-1342-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological functioning in children suspected for mitochondrial disease: the need for care

Abstract: Background: Mitochondrial diseases (MD) are generally serious and progressive, inherited metabolic diseases. There is a high comorbidity of anxiety and depression and limitations in daily functioning. The complexity and duration of the diagnostic process and lack of knowledge about prognosis leads to uncertainty. In this study, we investigated the psychological well-being of children who are suspected for MD and their parents. Methods: In total 122 children suspected for MD and their parents, received question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Our results therefore confirm a major deterioration in the quality of life of children and adolescents with MD corroborating what has previously been shown by several studies ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results therefore confirm a major deterioration in the quality of life of children and adolescents with MD corroborating what has previously been shown by several studies ( 44 , 45 ).…”
Section: Discussionsupporting
confidence: 93%
“…This re ects existing grey literature [3,5,30] and is consistent with ndings from condition-speci c studies which used diagnostic tools to measure anxiety and/or depression in rare disease patients and/or carers [20][21][22] and impact on quality of life. [17][18][19] Consistent with condition-speci c research [33][34][35][36], our ndings show that the negative impact on mental health can be chronic, and can occur or recur at different times such as during the 'diagnostic odyssey'; when a diagnosis is given; and while coming to terms with the condition. This highlights the periods when additional emotional support may be particularly important.…”
Section: Discussionsupporting
confidence: 82%
“…Factors related to service access were also likely related to the rarity of the condition, in particular the way care is coordinated; it is well established that care is often poorly coordinated for rare disease patients, many of whom have complex needs and are under the care of several doctors from different specialties. [4] Our ndings are consistent with previous condition-and country-speci c research into the psychological impact of the process of diagnosis [34][35][36], and the experiences of Australian families affected by rare diseases that found that delay in diagnosis and the perceived lack of knowledge among healthcare professionals were associated with anxiety and stress. [7] This study also reported that parents perceived the lack of knowledge among clinicians to be a leading cause of diagnostic delays, highlighting an interrelation between two emotional stressors.…”
Section: Factors Affecting Mental Healthsupporting
confidence: 88%
“…intelligence, and BMI following multivariate logistic regression analysis. It is known that the somatic complaints subscale of the CBCL is difficult to interpret in children with chronic disease, and the items could overlap with illness-specific symptoms (van de Loo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%